Characterization of Pseudomonas aeruginosa Isolated from Bovine Mastitis in Northern Jiangsu Province and Correlation to Drug Resistance and Biofilm Formability - Yicai Huang; Pengqiang Chen; Hainan Cao; Zheng Zhou; Tianle Xu (Animals)
This study aimed to provide experimental support for the prevention and treatment of Pseudomonas aeruginosa infections and to elucidate the epidemiological distribution of resistance and virulence genes of Pseudomonas aeruginosa from mastitis in dairy cows in the northern part of Jiangsu Province and their relationship with the biofilm-forming ability of the strains. Mastitis presents a significant challenge within dairy farming, adversely impacting the health of dairy cows and precipitating substantial economic losses in milk production. In this study, Pseudomonas aeruginosa (PA) was isolated and identified from mastitis milk samples in Jiangsu Province, China. In order to characterize the isolates, multilocus sequence typing (MLST), drug resistance phenotypes, virulence genes, and biofilm formations were detected. The isolation and identification of pathogenic bacteria from 168 clinical mastitis milk samples using 16S rRNA and PCR revealed 63 strains of Pseudomonas aeruginosa, which were determined to be highly homologous according to phylogenetic tree analysis. In addition, the MLST indicated five major ST types, namely ST277, ST450, ST571, ST641, and ST463. The susceptibility to 10 antimicrobials was determined, and it was found that 63 strains of Pseudomonas aeruginosa did not have a strong resistance to the antimicrobials in general. However, there were differences in the phenotypes’ resistance to antimicrobials among the different ST types. It was also found that the more resistant the strains were to antimicrobials, the lower the carriage of virulence genes detected. The biofilm content was measured using the semi-quantitative crystal violet method. It was found that there were a few strains with medium or strong biofilm-forming abilities. However, the number of virulence genes carried by the 63 strains of Pseudomonas aeruginosa was inversely proportional to the biofilm-forming ability. It was also found that there were significantly more Pseudomonas aeruginosa in the biofilm state than in the planktonic state and that strains with strong biofilm-forming abilities were more resistant to antimicrobials.